Pengaruh Media Audio Visual Terhadap Hasil Belajar Siswa Mata Pelajaran IPS Kelas V SDN 234 Palembang - Isnaini, Alpin; Armariena, Dian Nuzulia; Rizhardi, Rury (Indonesian Research Journal on Education, 2022)
The effect of audio-visual media on student learning outcomes for social studies subjects in class V SDN 234 Palembang The problem in this study after observation was that the learning outcomes of fifth grade students at SD Negeri 234 Palembang were not optimal, especially in social studies subjects. This study aims to determine whether or not the influence of audio-visual media on the learning outcomes of fifth grade students in Social Studies at SDN 234 Palembang. This experimental method uses a pre experimental design with a posttest design research design. The population in this study were all fifth grade students who took part in learning at SD Negeri 234 Palembang. Sampling using purposive sampling technique. Data collection techniques data using tests. Data analysis using t test which shows the value of tcount = 3.17 more than ttable(0.05) = 2.01 so that Ha is accepted. Likewise with the sig value of 0.46 > 0.05. Thus, there is an effect of Audio Visual media on learning outcomes in fifth grade students at SDN 234 Palembang.